EXPERIMENTAL MELTING OF A MODALLY HETEROGENEOUS MANTLE - Bulatov V.K.; Girnis A.V.; Brey G.P. (My University, 2002)
Melting of a spinel lherzolite with a spinel clinopyroxenite layer was investigated experimentally from 3.5 to 20 kbar and from 1200 to 1450 °C. The melt fraction in the spinel pyroxenite layer increases rapidly, and clinopyroxene disappears leaving olivine-spinel residua according to the reaction Cpx + Sp = Ol + Liq. The melt in the pyroxenite layer reacts with the surrounding lherzolite resulting in the formation of an essentially monomineral (olivine) zone with interstitial melt near the former pyroxenite. Melt compositions in the central melt pool are similar to those produced by other authors in melting experiments with peridotites similar to the bulk compositions of our samples. It is suggested that similar small-scale mantle heterogeneities (i.e. thin pyroxenite layers in lherzolite) may exert significant influence on mantle rheology and melt segregation, whereas melt compositions are not strongly affected and controlled by the dominating lherzolite lithology.